2009
DOI: 10.1007/s11255-009-9633-y
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin protects tissue perfusion in the experimental testicular torsion model

Abstract: Recently, anti-inflammatory and tissue protective effects of statins have been shown independent from its anti-hyperlipidemic effect. It has been shown that one of the statins, rosuvastatin, may reduce ischemia/reperfusion (I/R)-induced tissue injury in the brain, intestines, and heart. We planned an experimental study to evaluate the effect of rosuvastatin on I/R injury encountered after the detorsion of the testicular torsion. Rats were divided into three groups. In group 1, testis basal blood flow (basal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Previous researchers (Yurtc et al 2009) observed a loosening of cell-cell contacts in the testicular I/R and attributed these separations to shrinkage of both germ and Sertoli cells. Former studies (Karakaya et al 2010) reported that there was disorganization of germ cell structure and affection of their function. They explained disorganization by elevated level of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers (Yurtc et al 2009) observed a loosening of cell-cell contacts in the testicular I/R and attributed these separations to shrinkage of both germ and Sertoli cells. Former studies (Karakaya et al 2010) reported that there was disorganization of germ cell structure and affection of their function. They explained disorganization by elevated level of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of chemicals and drugs, such as oxygen radical scavengers, have been successfully used to reduce I/R injuries in animal models of testicular torsion, but few of these substances are currently in clinical use 14 . Karakaya et al 15 evaluated the effects of Rosuvastatin, a synthetic statin, in rats torted testes (2 hours ischemia / reperfusion 1 hour) and concluded that Rosuvastatin can protect tissue perfusion in the experimental testicular torsion model. Erol et al 16 investigated the effect of intraperitoneal vardenafil (1 mg/kg) administration during an ischemic period in a rat model of testicular torsion/detorsion (1 hour ischemia/4 hours reperfusion) and concluded that vardenafil reduced MDA levels and decreased ischemia/reperfusion cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…The rosuvastatin group had return of blood flow following detorsion equal to the control group (sham operation) and significantly better than the torsion group. [59] Interpretation of these results indicates that rosuvastatin may preserve or salvage tissue perfusion in an experimental testicular torsion animal model.…”
Section: Drugs To Modulate Ischemic Germ Cell Damagementioning
confidence: 97%
“…The theory is that these drugs can lead to improvement of the testicular function (particularly germ cell function) following an episode of torsion when the testis is salvaged. Although not tested in human testicular torsion, drugs such as vardenafil [57], sildenafil [58], rosuvastatin [59] and poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors [60, 61], and supplements such as coenzyme Q10 [62], lycopene [63] and ginkgo biloba [64] have been studied in rat models of testicular torsion.…”
Section: Drugs To Modulate Ischemic Germ Cell Damagementioning
confidence: 99%